Genetic parameters of growth and leaf traits and genetic gains with MGIDI in three Populus simonii × P. nigra families at two spacings - Wang, Tianxin; Ren, Jingshan; Huang, Qinjun; Li, Jinhua (Frontiers in Plant Science, 2024)
New genotypes of hybrid from the Aigeiros and Tacamahaca sections, which encompass economically important species of Populus L., have great potential to significantly enhance genetic gain from selection. Growth and its functional and structural determinants exhibiting a high level of variability are not only controlled by genetics, but also affected by environment, as well as genotype and environment interaction (G×E). The preceding research on the intersectional progenies derived from eight families (P. simonii × P. nigra) and their respective parents has indicated that leaf traits exhibiting robust genetic control were employed for selection of hybrid genotypes displaying multiple traits. The goals of this research with the progenies 3 families across two spacing trials were to (1) assess the GEI in progeny genotypes for multiple traits, (2) estimate the genetic parameters for important traits, (3) identify the genotypes with superior productive performance, adaptability, and genotypic stability using the MGIDI index, (4) select genotypes that exhibit high performance and genotypic stability across multiple traits using the MGIDI index. We found that the progeny genotypes showed considerable variation in growth and leaf morphology response to the spacings and genotype interaction effects were significant (P ≤ 0.001) for most of the traits studied in the progeny of each family and the joint family. The highest broad-sense heritability was observed for petiole length, while the lowest heritability values were recorded for stomatal length among the eight traits studied in both each family and the joint family. The MGIDI, assuming selection intensity of 15 %, identified 26, 25, 35, and 86 genotypes in the three families and the joint family, respectively. The selected hybrids of each family and the joint family exhibited the desired genetic gains, including positive gains for leaf area (6.87%-11.2%), petiole length (3.81%-13.7%) and plant height (1.30%-10.4%). The interpretation of strengths and weaknesses as illustrated by the MGIDI provides guidance for the breeders to develop poplar hybrids performed well in desired traits, such as growth and other yield contributors i.e. leaf traits. The tested progeny genotypes of three families provided a valuable addition to the hybrid selection for rapid juvenile growth.